2019
DOI: 10.1002/cpt.1311
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Anthracycline‐Induced Cardiotoxicity: Mechanisms, Pharmacogenomics, and Pluripotent Stem‐Cell Modeling

Abstract: Anthracycline‐induced cardiotoxicity ( ACT ) is a severe adverse drug reaction for a subset of children treated with anthracyclines as part of chemotherapy protocols. The identification of genetic markers associated with increased ACT susceptibility has clinical significance toward improving patient care and our understanding of the molecular mechanisms involved in ACT . Human‐induced pluripotent stem cell–derived cardiomyocytes represent a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 60 publications
1
44
0
1
Order By: Relevance
“…In an attempt to validate these associations in the setting of early onset severe ACT, our study identified that 14 out of 15 patients had at least one of the missense variants associated with cardiotoxicity to date. Nevertheless, incorporating these genetic markers into practice requires replication studies and further functional validation [41]. Importantly, both the onset of cardiotoxicity after anthracycline treatment and the dose at which cardiotoxicity was observed did not correlate with the burden of variants within this cohort.…”
Section: Discussionmentioning
confidence: 91%
“…In an attempt to validate these associations in the setting of early onset severe ACT, our study identified that 14 out of 15 patients had at least one of the missense variants associated with cardiotoxicity to date. Nevertheless, incorporating these genetic markers into practice requires replication studies and further functional validation [41]. Importantly, both the onset of cardiotoxicity after anthracycline treatment and the dose at which cardiotoxicity was observed did not correlate with the burden of variants within this cohort.…”
Section: Discussionmentioning
confidence: 91%
“…More novel AC molecules such as Epirubicin and idarubicin and the structurally related molecule mitoxantrone have been proposed as less cardiotoxic variants of DOX. However, over the years, all types of AC have been shown to cause AC-induced cardiac toxicity [ 23 ].…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%
“…These genes play roles in DNA damage pathways, oxidative stress response, iron metabolism, drug transport, and sarcomere function. Mostly, the ABCC, CBR3, and SLC28A3 genes have emerged in the majority of studies cited, emphasizing their important role in the development of AC-related heart disease [ 23 ].…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%
“…Unveiling the genetic variants that contribute to AIC is of upmost importance since it may give the clinicians the opportunity to identify patients at risk prior the treatment, and potentially modify the therapeutic regimens by using alternative drugs or cardioprotective agents. Early candidate gene association studies (CGAS) and genomewide association studies (GWAS) have started to reveal the first genes, that are primarily related to drug metabolism and transport, iron metabolism, DNA repair, oxidative stress, and calcium homeostasis, with no genes being directly linked to mitochondrial function regulation (123,124). However, given the small sample sizes of these studies, additional work is warranted to conclusively validate these variants and to discover new genes implicated in AIC susceptibility.…”
Section: Future Perspectivesmentioning
confidence: 99%